Border Check and Security from the Perspective of Travel Document Forgery Before and Following Schengen - Balla, József (Magyar Rendészet, 2019)
The components of border check have a significant impact on the safety of a country or a region. The composition of border traffic by nationality and the security of travel documents from a travel document protection point of view, basically, determine the risk classification/insecurity of a particular border crossing point. Those travel documents which have lower travel document protection become subject to official document forgery in greater numbers. The detection of these illegal acts depends on the preparedness of the person carrying out the control which also means that this person is the key to success.